2019
DOI: 10.1021/acscatal.9b01748
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Asymmetric Synthesis of N-Aryl-Functionalized Amino Acids and Substituted Pyrazolidinones

Abstract: N-arylated α-amino acids and pyrazolidin-3-ones are widely being used as chiral building blocks for pharmaceuticals and agrochemicals. Here we report a biocatalytic route for the asymmetric synthesis of various N-arylated aspartic acids applying ethylenediamine-N,N′-disuccinic acid lyase (EDDS lyase) as a biocatalyst. This enzyme shows a broad substrate scope, enabling the addition of a variety of arylamines to fumarate with high conversions, yielding the corresponding N-arylated aspartic acids in good isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Recently, we reported that ethylenediamine-N,N 0 -disuccinic acid (EDDS) lyase naturally catalyzes a reversible two-step sequential addition of ethylenediamine (2) to two molecules of fumaric acid (3), giving (S)-N-(2-aminoethyl)aspartic acid (AEAA, 4) as an intermediate and (S,S)-EDDS (5) as the final product (Table 1A). 12 EDDS lyase was subsequently found to have broad substrate promiscuity, [13][14][15] accepting a wide range of amino acids with terminal amino groups (6a-k) for regio-and stereoselective addition to fumarate, thus providing a straightforward biocatalytic method for the asymmetric synthesis of AMA (1a), AMB (1b), and related aminocarboxylic acids (1c-k, Table 1B). 13 To further explore the substrate scope of EDDS lyase, as well as to prepare a small library of EDDS derivatives as potential NDM-1 inhibitors, 16 we here describe the EDDS-lyase catalyzed reaction of fumaric acid with various diamines containing different aliphatic linkers between the two amino functional groups (7a-i) ( Table 2).…”
mentioning
confidence: 99%
“…Recently, we reported that ethylenediamine-N,N 0 -disuccinic acid (EDDS) lyase naturally catalyzes a reversible two-step sequential addition of ethylenediamine (2) to two molecules of fumaric acid (3), giving (S)-N-(2-aminoethyl)aspartic acid (AEAA, 4) as an intermediate and (S,S)-EDDS (5) as the final product (Table 1A). 12 EDDS lyase was subsequently found to have broad substrate promiscuity, [13][14][15] accepting a wide range of amino acids with terminal amino groups (6a-k) for regio-and stereoselective addition to fumarate, thus providing a straightforward biocatalytic method for the asymmetric synthesis of AMA (1a), AMB (1b), and related aminocarboxylic acids (1c-k, Table 1B). 13 To further explore the substrate scope of EDDS lyase, as well as to prepare a small library of EDDS derivatives as potential NDM-1 inhibitors, 16 we here describe the EDDS-lyase catalyzed reaction of fumaric acid with various diamines containing different aliphatic linkers between the two amino functional groups (7a-i) ( Table 2).…”
mentioning
confidence: 99%
“…Her current research interests include exploring the reactivity of enzymes from natural product biosynthesis pathways for producing pharmaceutically relevant molecules. [16][17][18][19][20][21] Ph, aryl H H RgPAL, AvPAL, PcPAL phenylalanine, β-aryl α-alanines [6,[22][23][24][25][26] chelating compound widely used in industry for a wide range of applications, such as soil remediation, paper manufacturing, waste water treatment and so on. (S,S)-EDDS was isolated as a secondary metabolite from the actinomycete Amycolatopsis japonicum, hypothetically serving as a scavenger of zinc (zincophore) and its bioproduction was strictly repressed by zinc.…”
Section: Properties Structure and Catalytic Mechanismmentioning
confidence: 99%
“…Another synthetic application of EDDS lyase was demonstrated by the biocatalytic asymmetric synthesis of various Narylated l-aspartic acids and the chemoenzymatic synthesis of challenging 2-aryl-5-carboxylpyrazolidin-3-ones ( Figure 5). [19] Especially, pyrazolidinones are widely found as core structures in pharmaceutically active molecules including lipoxygenase inhibitors ( Figure 4) and anti-Alzheimer agents. [19] EDDS lyase accepted a broad range of arylamines and arylhydrazines as substrates for addition to fumarate, giving the corresponding N-arylated l-aspartic acids and N-(arylamino)aspartic acids, respectively, with good isolated yields and excellent enantiopurity.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N ‐(hetero)arylation of amino acids with heteroaryl and aryl halides have been carried out using copper and palladium as well as combined catalysts with different types of ligands and N ‐heterocyclic carbenes . The catalytic N ‐arylation of amino acid esters and N ‐modification with phenol are also known whilst the use of biocatalysts is gaining momentum . Other notable arylation methods include nucleophilic aromatic substitution, three‐component aryne coupling reaction and hypervalent iodine chemistry .…”
Section: Introductionmentioning
confidence: 99%